68.2k views
4 votes
What is the factored form of
X^3-1

User Mssm
by
6.2k points

2 Answers

7 votes
Notice how both terms are perfect cubes. You can factor using the difference of cubes formula:


a^3-b^3=(a-b)(a^2+ab+b^2) \\ \\ x^3-1 = x^3- 1^3 = (x-1)(x^2+x+1)

The factored form of x³ - 1 is (x - 1)(x² + x + 1).
User Jisaacstone
by
5.9k points
6 votes
keeping in mind that

1² = 1
1³ = 1
1⁴ = 1
1¹⁰⁰⁰⁰⁰⁰ = 1


\bf \textit{difference and sum of cubes} \\\\ a^3+b^3 = (a+b)(a^2-ab+b^2) \\\\ a^3-b^3 = (a-b)(a^2+ab+b^2)\\\\ -------------------------------\\\\ x^3-1\implies x^3-1^3\implies (x-1)(x^2+1x+1^2) \\\\\\ (x-1)(x^2+x+1)
User RockWorld
by
6.1k points